Combination Therapy of Mithramycin A and Immune Checkpoint Inhibitor for the Treatment of Colorectal Cancer in an Orthotopic Murine Model - Dutta, Rinku; Khalil, Roukiah; Mayilsamy, Karthick; Green, Ryan; Howell, Mark; Bharadwaj, Srinivas; Mohapatra, Shyam S.; Mohapatra, Subhra (Frontiers in Immunology, 2021)
The axis of Programmed cell death-1 receptor (PD-1) with its ligand (PD-L1) plays a critical role in colorectal cancer (CRC) in escaping immune surveillance and blocking this axis has been found to be effective in a subset of patients. Although blocking PD-L1 has been shown to be effective in 5 - 10% of patients, the majority of the cohorts show resistance to this checkpoint blockade (CB) therapy. Multiple factors assist in the growth of resistance to CB among which T cell exhaustion and immunosuppressive effects of immune cells in the tumor microenvironment (TME) play a critical role along with other tumor intrinsic factors. We have previously shown the polyketide antibiotic, Mithramycin-A (Mit-A), an effective agent in killing cancer stem cells (CSCs) in vitro and in vivo in a subcutaneous murine model. Since TME plays a pivotal role in CB therapy, we tested immunomodulatory efficacy of Mit-A with anti-PD-L1 mAb (αPD-L1) combination therapy in an immunocompetent MC38 syngeneic orthotopic CRC mouse model. Tumors and spleens were analyzed by flow cytometry for the distinct immune cell populations affected by the treatment, in addition to RT-PCR for tumor samples. We demonstrated the combination treatment decreases tumor growth, thus increasing the effectiveness of the CB. Mit-A in presence of αPD-L1 significantly increased CD8+ T cell infiltration and decreased immunosuppressive granulocytic myeloid-derived suppressor cells and anti-inflammatory macrophages in the TME. Our results revealed Mit-A in combination with αPD-L1 have the potential for augmented CB therapy by turning an immunologically “cold” into “hot” TME in CRC.